Tree species community spatial structure in a terra firme Amazon forest, Brazil - Emidio da Silva, Kátia; Martins, Sebastião Venâncio; Fortin, Marie Josée; Ribeiro, Milton Cezar; de Azevedo, Celso Paulo; Álvares Soares Ribeiro, Carlos Antonio; Terra Santos, Nerilson (BOSQUE, 2017)
All trees with diameter at breast height dbh ≥ 10.0 cm were stem-mapped in a "terra firme" tropical rainforest in the Brazilian Amazon, at the EMBRAPA Experimental Site, Manaus, Brazil. Specifically, the relationships of tree species with soil properties were determined by using canonical correspondence analyses based on nine soil variables and 68 tree species. From the canonical correspondence analyses, the species were grouped into two groups: one where species occur mainly in sandy sites, presenting low organic matter content; and another one where species occur mainly in dry and clayey sites. Hence, we used Ripley’s K function to analyze the distribution of species in 32 plots ranging from 2,500 m2 to 20,000 m2 to determine whether each group presents some spatial aggregation as a soil variations result. Significant spatial aggregation for the two groups was found only at over 10,000 m2 sampling units, particularly for those species found in clayey soils and drier environments, where the sampling units investigated seemed to meet the species requirements. Soil variables, mediated by topographic positions had influenced species spatial aggregation, mainly in an intermediate to large distances varied range (≥ 20 m). Based on our findings, we conclude that environmental heterogeneity and 10,000 m2 minimum sample unit sizes should be considered in forest dynamic studies in order to understand the spatial processes structuring the "terra firme" tropical rainforest in Brazilian Amazon.